Notas sobre Andrés Bello y América Latina - Barros Charlín, Raymundo (Estudios Internacionales, 1982)
The "great men" of Latin American thought were contemporaries of the Colony, with all its institutions and realities. That was their "circumstance." We could hardly ask Andrés Bello for a unique body of ideas about his cultural, political and legal approaches to be applied in Latin America, or in a specific country in the region. Andrés Bello should be neither more nor less than the prompt, learned and prudent consultant to guide, enlighten and inform the authority. However, there are enough elements of judgment to measure his concern for Latin America and to promote the creation of solid ties between nations. Two hundred years have passed since its birth and the countries of the region show mutual misgivings and breakdowns in the collective will. Latin America, which concerned him so much, that "natural community" of republics, has not yet threaded its integration in a categorical way.